Root Cause Analysis Framework for Regulatory Compliance in Philippine Aviation Training - Dela Peña, Arthur; Clariza, Jefferson; Tiansay, Eric; Ganal, Mark Anthony (Journal of Technical Education and Training, 2025)
Approved Training Organizations (ATOs) in the Philippines operate under the regulatory oversight of the Civil Aviation Authority of the Philippines (CAAP), which conducts annual audits to assess compliance with the Philippine Civil Aviation Regulations (PCAR) and ICAO Annex 1. Despite these inspections, recurring compliance gaps, particularly in documentation, instructional delivery, and internal quality assurance, suggest persistent systemic deficiencies. This study addresses these challenges by introducing a Root Cause Analysis (RCA)– based framework designed to strengthen regulatory compliance in aviation training institutions. Employing a qualitative case study design, the research analyzed CAAP audit reports, Corrective Action Requests (CARs), and internal quality documents from three ATOs. Methodological rigor was ensured through data triangulation, manual coding, and thematic analysis using NVivo software. RCA tools, including the 5 Whys and Fishbone Diagrams, were applied to trace visible deficiencies to underlying causes across organizational domains such as people, process, tools, and policy. The findings revealed institutional weaknesses in audit preparedness, instructional oversight, and quality monitoring that significantly contribute to compliance failures. The primary contribution is a systems-oriented RCA framework that embeds proactive compliance mechanisms within ATOs’ internal quality assurance functions, featuring a feedback loop linking RCA, CAPA escalation, targeted training, and internal audits. Policy recommendations are also proposed to enhance CAAP’s audit communication and CAP evaluation protocols, promoting a shift from reactive enforcement to developmental oversight. By positioning RCA as both an investigative and governance tool, this study offers a transferable model for enhancing regulatory resilience in aviation training systems across similarly regulated environments worldwide.